Regulation of the Autophagic Bcl-2/Beclin 1 Interaction - Decuypere, Jean-Paul (MDPI, 2012)
Autophagy is an intracellular degradation process responsible for the delivery of cellular material to the lysosomes. One of the key mechanisms for control of autophagy is the modulation of the interaction between the autophagic protein Beclin 1 and the members of the anti-apoptotic Bcl-2 family (e.g., Bcl-2, Bcl-X(L) and Mcl-1). This binding is regulated by a variety of proteins and compounds that are able to enhance or inhibit the Bcl-2/Beclin 1 interaction in order to repress or activate autophagy, respectively. In this review we will focus on this interaction and discuss its characteristics, relevance and regulation.